Relationship Between Fulfilling Balance Nutrition and Stunting in Toddlers Aged 24-26 Months - Rotua Suriany Simamora; Puri Kresnawati (Universitas Muhammadiyah Semarang, 2023)
Stunting is a chronic malnutrition problem caused by insufficient nutritional intake for a long time due to feeding that is not in accordance with nutritional needs. Stunting can be a major threat to the quality of Indonesian people and also a threat to the nation's competitiveness. This can occur because stunted children are not only disturbed by their physical growth, but also their brain development which greatly affects their ability and achievement at school, productivity and creativity at productive age. This research was conducted to determine the relationship between the fulfillment of balanced nutrition and the incidence of stunting in children under five. The design of this study was an observational analytic epidemiology using cross sectional. The population in this study were 200 respondents with a quota sampling technique. Furthermore, bivariate analysis was carried out using the chie square. The results showed that the majority of the level of fulfillment of balanced nutrition in toddlers was 143 (71.5%) and the incidence of stunting was mostly not stunted by 161 respondents (80.5%). Analysis of data using the chi square test with a significant level of 0.05 obtained p value is 0.000, which means that the value is smaller than the value of the significant level (0.000 <0.05) which indicates a relationship between the fulfillment of balanced nutrition and the incidence of stunting in children under five. The results of statistical data analysis also showed an Odds Ratio (OR) of 0.119 which means that the fulfillment of unfulfilled nutrition will have a chance of 0.119 with the incidence of stunting compared to the fulfillment of fulfilled balanced nutrition.